Risk factors for non-benefit of implantable cardioverter defibrillator therapy - Fabienne Kreimer; Marie Lewenhardt; Ibrahim El-Battrawy; Arash Haghikia; Michael Gotzmann (Scientific Reports)
Abstract Studies have demonstrated overall prognostic benefits of ICD implantation in patients at increased risk of sudden cardiac death. However, results are inconsistent in certain subgroups. This study aims to evaluate the prognostic implications of comorbidities on ICD outcomes and compare trends in patient selection and outcomes over a decade-long inclusion period. This study analysed 422 patients undergoing ICD implantation between 2011 and 2020. The study endpoint “no-benefit” was characterized by death from any cause occurring without prior appropriate ICD therapy. Benefit of ICD implantation was defined as either receiving appropriate ICD therapy before death or surviving until the end of the observation period. During a mean follow-up of 4.2 ± 3.0 years, no-benefit of ICD implantation was observed in 84 patients (20%). Independent risk factors for no-benefit were age ≥ 68 years (HR 4.599, p < 0.001), anemia (HR 2.549, p < 0.001), peripheral artery disease (HR 2.066, p = 0.007), and chronic obstructive pulmonary disease (HR 1.939, p = 0.014). Subgroup analysis by age < 68 years and ≥ 68 years demonstrated that the risk of no-benefit increases with age and comorbidities. When comparing patients with ICD implantation in 2011–2015 with those in 2016–2020, there were no significant differences in one-, two- and three-year-no-benefit rates. Different comorbidities were associated with no-benefit in the early and late implantation groups. Risk factors such as older age and specific comorbidities are associated with a higher likelihood of no-benefit from ICD implantation. A careful patient selection and consideration of individual risk factors besides advanced age is important.